A Review of An Interactive Augmented Reality Customization Clothing System Using Finger Tracking Techniques as Input Device - Liying Feng; Ng, Giap Weng; Liyao Ma (Springer, Singapore, 2020)
This paper mainly focuses on the review of applications in Augmented Reality (AR) technology in the field of clothing customization using finger tracking techniques as input device. Review the influence and role of AR technology in the clothing customization industry. A comparative analysis of the technological advances and technical deficiencies embodied in the virtual fitting software developed by the world in the past 10 years using AR technology. Through research and comparison, a personalized clothing customization system based on AR technology is proposed. The system can enhance people’s experience and interaction with the fashion design process and improve the satisfaction of clothing customization using finger techniques as input device.